2011
DOI: 10.1016/j.jnucmat.2011.07.004
|View full text |Cite
|
Sign up to set email alerts
|

First principles study of hydrogen behaviors in hexagonal tungsten carbide

Abstract: Understanding the behavior of hydrogen in hexagonal tungsten carbide (WC) is of particular interest for fusion reactor design due to the presence of WC in the divertor of fusion reactors. Therefore, we use first-principles calculations to study the hydrogen behavior in WC. The most stable interstitial site for the hydrogen atom is the projection of the octahedral interstitial site on tungsten basal plane, followed by the site near the projection of the octahedral interstitial site on carbon basal plane. The bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In previous theoretical studies, impurities have been found to interact strongly with the intrinsic defects and hydrogen in tungsten, which sheds light on the influence mechanism of impurities on the hydrogen retention, especially for carbon [16][17][18][19][20]. However, little theoretical work has been reported about the influences of nitrogen on hydrogen dissolution and diffusion in tungsten.…”
Section: Introductionmentioning
confidence: 99%
“…In previous theoretical studies, impurities have been found to interact strongly with the intrinsic defects and hydrogen in tungsten, which sheds light on the influence mechanism of impurities on the hydrogen retention, especially for carbon [16][17][18][19][20]. However, little theoretical work has been reported about the influences of nitrogen on hydrogen dissolution and diffusion in tungsten.…”
Section: Introductionmentioning
confidence: 99%
“…This fourth and final stage is related to deuterium bonded to carbon and accounts for only a small fraction of the total trapped inventory. It should be noted that the binding energy between deuterium atoms in the above sites is calculated to be negative [62], suggesting molecule formation is unfavourable.…”
Section: (D) Plasma-surface Interactionmentioning
confidence: 99%
“…These studies can provide some design tools toward minimizing hydrogen isotope retention. First of all, diffusion is faster in the c-axis of WC [62,63], suggesting that strongly textured materials would enable a directional dependence to the inventory build-up. Secondly, because trapping is dominated by the presence of interstitials and vacancies, both of which are intrinsic defects caused by deviations from stoichiometry, the carbon content can and should be properly controlled.…”
Section: (D) Plasma-surface Interactionmentioning
confidence: 99%
“…On the other hand, WC has been the subject of many atomic-scale computational studies, including investigation of bulk properties, point defects, ,, self-diffusivity, radiation damage, , and gas retention. , Previous DFT work ,, has shown that in dilute conditions, C vacancies are the most easily accommodated intrinsic point defects, followed by C interstitials (trigonal site on the C sublattice) and W vacancies, while W interstitials are highly unfavorable. This is evident from the formation energies of the respective defects, reproduced in Table .…”
Section: Introductionmentioning
confidence: 99%